First Evidence of Entamoeba Parasites in Australian Wild Deer and Assessment of Transmission to Cattle - Huaman, Jose L.; Pacioni, Carlo; Kenchington-Evans, Lily; Doyle, Mark; Helbig, Karla J.; Carvalho, Teresa G. (Frontiers in Cellular and Infection Microbiology, 2022)
Australian wild deer populations have significantly expanded in size and distribution in recent decades. Due to their role in pathogen transmission, these deer populations pose a biosecurity risk to the livestock industry. However, little is known about the infection status of wild deer in Australia. The intestinal parasite Entamoeba bovis has been previously detected in farm and wild ruminants worldwide, but its epidemiology and distribution in wild ruminants remain largely unexplored. To investigate this knowledge gap, faecal samples of wild deer and domestic cattle from south-eastern Australia were collected and analysed for the presence of Entamoeba spp. using PCR and phylogenetic analysis of the conserved 18S rRNA gene. E. bovis parasites were detected at high prevalence in cattle and wild deer hosts, and two distinct Entamoeba ribosomal lineages (RLs), RL1 and RL8, were identified in wild deer. Phylogenetic analysis further revealed the existance of a novel Entamoeba species in sambar deer and a novel Entamoeba RL in fallow deer. While we anticipated cross-species transmission of E. bovis between wild deer and cattle, the data generated in this study demonstrated transmission is yet to occur in Australia. Overall, this study has identified novel variants of Entamoeba and constitutes the first report of Entamoeba in fallow deer and sambar deer, expanding the host range of this parasite. Epidemiological investigations and continued surveillance of Entamoeba parasites in farm ruminants and wild animals will be required to evaluate pathogen emergence and transmission to livestock.